Peran Strategis UMKM dalam Mendorong Pertumbuhan Ekonomi Berkelanjutan di Indonesia - Suci Ramadani; Dilla Amelia Ramadhani; Muhammad Ikrom; Lokot Muda Harahap (FEB Universitas Maritim Semarang, 2025)
Micro, Small and Medium Enterprises are one of the most important pillars of the economy in Indonesia. MSMEs contribute significantly to Gross Domestic Product, employment, and regional development through income equality. This study attempts to obtain relevant answers regarding the strategic role of MSMEs in sustainable economic development in Indonesia, as well as the obstacles faced by this sector. Despite the government's role in sustainably encouraging MSMEs, this study shows that MSMEs still have difficulty accessing capital, government policies, and digitalization. This study uses a descriptive method to identify data that produces a good understanding of the factors that build the success of MSMEs. The results of the study show that the contribution of MSMEs to GDP is around 61.07%, employing 97% of the total number of jobs, namely MSMEs are quite important for the government and other stakeholders in supporting the role of MSMEs in inclusive and sustainable economic development.